Will Cause-Related Marketing Affect the American and Filipino College Students’ Purchase Intention? - Baurista, Reynaldo, Jr. (Animo Repository, 2020)
This study aims to examine the attitudes of American and Filipino college students and their intention to join the cause-related marketing (CRM) campaign. There were 200 Filipino and 180 American college students who joined the survey. The respondents were marketing majors. Using the theory of reasoned action (TRA), the results suggest a significant impact of religiosity, social influence, and attitude on the intention to join the CRM campaign. The results show that social influence has a positive relationship with attitude and intention to join CRM only in the U.S. Religiosity has a positive relationship with attitude and intention to join CRM in both countries. The results highlight the impact of cultural differences and exposure to CRM on consumer attitude and intention to participate in CRM across countries. This study suggests that marketers should design relevant CRM campaigns across countries.